A reply to “Estimating a bilateral J-curve between the UK and the euro area: An asymmetric analysis” - Michail, Nektarios A. (My University, 2021)
In 2018, I published an article in this journal aiming to examine whether the UK could potentially benefit from the depreciation of the pound following the Brexit decision. During this year's issue, a study by Bahmani-Oskooee and Karamelikli (2021) suggested that the findings of said article were based on sign misinterpretation. In this article, I explain that the misunderstanding that has arisen is due to an incorrect definition of a variable in the appendix. When the revised definition is taken into consideration, the conclusions reached still hold.
Keywords: Brexit; Euro area; J-curve; Trade balance